Peculiarities of hemostasis changes under the influence of different regimens of antiplatelet therapy in patients with Q-wave myocardial infarction - S. M. Kyselov (Zaporozhye State Medical University, 2014)
Aim. In order to study the influence of different regimens of antiplatelet therapy on the state of coagulation and aggregation hemostasis, intracardiac hemodynamics, incidence of post-infarction aneurysm and thrombus formation in the left ventricular cavity in patients with Q-wave myocardial infarction after thrombolysis, 123 people were examined. Methods and results. All participants underwent echocardiography, the study of coagulation and aggregation hemostasis, levels of protein C, von Willebrand factor and adhesion molecules sVCAM-1 were determined. Conclusion. Under the influence of the treatment reduction in aggregation and procoagulant activity of blood serum and activation of fibrinolytic processes were revealed, accompanied by improvement of left ventricular pumping and systolic function, diastolic dysfunction transformation from impaired relaxation into pseudonormal type.